The legality of Boster Pro Online Game Transactions Based On Fatwa Assembly Of Indonesian (MUI) No. 116/DSN-MUI/ix/2017 About Sharia Electronic Money - Haris Fadillah; M. Syukri Al Bani Nasution; Ramadhan Syahmedi; Mhd. Yadi Harahap (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2022)
This study aimed to describe the mechanism of buying and selling Diamonds in the online game Boster Pro based on the DSN MUI fatwa Number 110/DSN-MUI/IX/2017 on buying and selling Diamonds in the Boster Pro game. This type of research is normative law, which uses materials from written regulations or other normative legal materials. The study results concluded that the online game boster pro is a game to play slots, cards, and other betting games, and whoever often wins will get a lot from the bet. The bet is made using Diamonds (virtual coins) instead of Diamonds to play the game. In the Boster Pro game, Diamonds are provided on a limited basis; the more often gamers play games, the fewer Diamonds in the game. Then, gamers are looking for alternatives to get these by buying and selling transactions, namely by buying Diamonds belonging to luckier people. Gamers do this so they can continue to play the game. According to the DSN MUI Fatwa Number 110/DSN-MUI/IX/2017, in the buying and selling transaction of the Diamon game Boster Pro, the consent and acceptance are clear because the perpetrators of the buying and selling transactions are in a conscious state. However, according to the MUI, traded objects contain elements of maysir because they benefit from betting on a game. The next reason, the object of buying and selling is unclear and has no real form